2007
DOI: 10.1080/00207540600942268
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing knowledge sharing in PLM: a progression towards the use of heavy weight ontologies

Abstract: The drive to maximise the potential benefits of decision support systems continues to increase as industry is continually driven by the competitive needs of operating in dynamic global environments. The more extensive information support tools which are becoming available in the PLM world appear to have great potential but require a substantial overhead in their configuration. However, sharing information and knowledge in crossdisciplinary teams and across system and company boundaries is not straightforward a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 5 publications
0
50
0
1
Order By: Relevance
“…Thus, the IMKS approach allows the derivation of specialised knowledge bases as repositories for designers and planners alike, without the need to commit to a fixed master model. In that sense, the heavyweight ontology dimension of this work builds on top of the current perceived advantages of applying formal ontologies within a PLM context to aid the process of semantic interoperability and knowledge exchanges [3,6,7,16,17].…”
Section: Ontologies Of Core Conceptsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the IMKS approach allows the derivation of specialised knowledge bases as repositories for designers and planners alike, without the need to commit to a fixed master model. In that sense, the heavyweight ontology dimension of this work builds on top of the current perceived advantages of applying formal ontologies within a PLM context to aid the process of semantic interoperability and knowledge exchanges [3,6,7,16,17].…”
Section: Ontologies Of Core Conceptsmentioning
confidence: 99%
“…This, therefore, raises an important concern from the point of view of semantic knowledge capture and sharing. It has been shown that OWL is limited in representing complex manufacturing constraints and process semantics [3,6]. Furthermore, although some efforts have utilised OWL with rule languages [20,27], these rule languages do not benefit from full first order logic constructs.…”
Section: Combined Plm and Knowledge-based Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lutters et al (2000) worked to apply information management based on an ontological approach on design and engineering processes under special consideration of manufacturing, i.e., process planning and cost estimation. Lemaignan et al (2006) designed an upper level manufacturing ontology (MASON), and Young et al (2007) showed the benefits of applying ontologies to support knowledge sharing in PLM with a focus on manufacturing processes. Giménez et al (2008) defined a product ontology to model complex product (the PRONTO ontology).…”
Section: Introductionmentioning
confidence: 99%